Interface of a Tool for Buying New Houses Online : An improvement of Design Studio from an environmentally friendly perspective - Swén, Sanna (Luleå tekniska universitet, Institutionen för ekonomi, teknik, konst och samhälle, 2022)
This project is a master’s thesis in Industrial Design that has been conducted in the spring of 2022 at Luleå University of Technology. The project is a cooperation with the company Neava and is about improving their online tool Design Studio. The goal of the project is to improve the online tool from an environmentally friendly perspective, i.e., how information is presented regarding material’s impact on the environment and how energy efficient the house will be when all the choices have been made. Today, there are two different interfaces of Design Studio. One that is based on specific requirements from a customer, and another that is designed for sellers. None of these interfaces provides the user with information about how the materials are affecting the environment. Today it is important to think about the materials and energy efficiency when new houses are being built to create a sustainable future. The work has been conducted by the process Design Thinking, which is an iterative process that is performed in five different phases: empathize, define, ideate, prototype, and test. In the first phase, an understanding of the user was created, this was conducted through interviews and a survey. In the second phase, the user was identified, and user needs were established. In the third phase, different ideas and concepts were generated and then evaluated by users. In the fourth phase, a clickable prototype was created in the program Adobe XD. In the fifth phase, the prototype was tested on users and later improved based on the results. The final result is a clickable prototype that informs the user about the available materials and how they are affecting the environment. The materials are categorized into three different groups: red, yellow, and green. If a material is in the red category, it indicates that the material is the worst for the environment. If a material is in the yellow category, it indicates that the material is okay for the environment. If a material is in the green category, it indicates that ...